Enhancing Organizational Readiness Through AI: Evidence of Management Performance Mediation in Private Hospitals - Khomeiny Yunior; Syaifuddin Syaifuddin; Robert Tua Siregar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The growth of artificial intelligence (AI) in healthcare is causing big shifts in management roles and how ready organizations are, especially in private hospitals. In Medan City, rising competition, a small healthcare workforce, and strict accreditation requirements all make it even more important to use digital technology to make operations more efficient. This study seeks to examine the impact of AI on organizational readiness, utilizing management performance as a mediating variable. Quantitative approaches were employed via a survey of managers and administrative personnel at private hospitals, and the data were analyzed using path analysis with SPSS. The findings indicate that AI exerts a favorable and considerable influence on management performance, which in turn directly enhances organizational readiness. Additionally, managerial performance has been demonstrated to mediate the relationship between AI and organizational readiness. These findings address a research gap concerning the mechanisms of AI's role in the managerial context of hospitals in developing countries and offer practical implications for fortifying digital strategies, cultivating human resource competencies, and augmenting organizational capabilities in response to technology-driven healthcare transformation.